2018
DOI: 10.1002/slct.201801720
|View full text |Cite
|
Sign up to set email alerts
|

Five Diverse Multidimensional Polycarboxylate–Based Mixed–Ligand Coordination Polymers with Different N,N′–Donor Ligands: Synthesis, Characterization and Their Sorption Study

Abstract: Five mixed ligand coordination polymers (CPs) explicitly {[Cu2(btp)(2,5‐pyrdc)2H2O].4H2O}n (1), {[Cu(bte)0.5(2,5‐pyrbdc)H2O].1.5H2O}n (2), {[Cu(bte)(1, 2,4,5‐btc)0.5(H2O)].3H2O}n (3), {[Co(4‐bpdh)(1, 2,4,5‐btc)0.5(H2O)(MeOH)]}n (4), and {[Co(4‐bpdb)1.5(1,2,4,5‐btc)(H2O)4].4H2O(MeOH)}n (5) have been synthesized by using two polycarboxylates 2,5‐pyridinedicarboxylate (2,5‐pyrdc2–), 1,2,4,5‐benzenetetracarboxylate (1,2,4,5‐btc4–) and four differently polar N–donor ligands. Here, two different transition metals Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…For the inclusion of multifunctionality, in a single framework, it should be very well tuned with the logical incorporation of metal and ligand/functional groups so that it can display all the required applications in an intriguing way. Among different applications of PCPs, carbon dioxide sorption at different conditions has been a well established fact by many groups during the last few decades. On the other hand, another important application, which has just recently drawn a great deal of attention, is electrical conductivity. These two applications individually have been exhibited by numerous PCPs because of their multifaceted use in different aspects, but it has been sparingly reported that compounds exhibit these two applications together. , Hence, to construct a PCP showing both functionalities together, careful design and judicious consideration of synthetic factors are highly required. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the inclusion of multifunctionality, in a single framework, it should be very well tuned with the logical incorporation of metal and ligand/functional groups so that it can display all the required applications in an intriguing way. Among different applications of PCPs, carbon dioxide sorption at different conditions has been a well established fact by many groups during the last few decades. On the other hand, another important application, which has just recently drawn a great deal of attention, is electrical conductivity. These two applications individually have been exhibited by numerous PCPs because of their multifaceted use in different aspects, but it has been sparingly reported that compounds exhibit these two applications together. , Hence, to construct a PCP showing both functionalities together, careful design and judicious consideration of synthetic factors are highly required. …”
Section: Introductionmentioning
confidence: 99%
“…It is evident that the proper pore dimensions and pore environment are required for better CO 2 sorption, which can help to accommodate the CO 2 molecules by extensive interaction with the pore wall. Furthermore, electron-rich metal centers connected by a suitable pathway of bridging ligand for effective charge conduction are essential, for better results in electrical conductivity and photo response behavior over such conductivity. , Therefore, to obtain both functionalities in a single framework, proper linkers are required which can simultaneously produce a suitable pore as well as be useful as a better conductive medium. , To obtain these requirements, the mixed ligand CPs, usually containing two different types (dicarboxylate and N,N′-donor linker) of linkers, are found to be extremely nice, because they are sufficiently supportive for achieving a functional architecture. , In such cases, the presence of an aromatic moiety in one of those linkers and the presence of electron-rich metal centers can undoubtedly enhance the flow of charge between two consecutive metal centers giving a meaningful outcome for electrical conductivity. , On the other hand, linkers having polar functional groups (CH 3 , C 2 H 5 , F – , OH – , NH 2 , etc.) can play a crucial role in showing significant effects on carbon dioxide sorption by the synthesized mixed ligand PCP. , …”
Section: Introductionmentioning
confidence: 99%
“…Different studies have shown that MOFs are certainly a good candidate for CO 2 capture. In particular, mixed ligand metal–organic frameworks , have proven to be an extremely suitable material for this purpose due to their simple synthetic procedure and tunable framework. , Although a lot of mixed ligand MOFs, showing selective carbon dioxide sorption, have been reported, the introduction of tuned and well decorated pores inside the structure eventually gives a positive outcome. Since pore dimension, pore environment, and polarity of the pores inside the framework are the key parameters for better carbon dioxide adsorption, the appropriate choice of the mixed ligands to build up the networks with proper pores is one of the key factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to control the final structures of MOFs, because they may be influenced by many factors, including metal center, organic ligand, synthetic method, temperature, solvent, reactant ratio, pH value, counterion, auxiliary ligand, etc . Among the various factors, organic ligand is believed to be the most critical one, whose type, shape, rigidity, length, substituent group can lead to diversity of the whole framework …”
Section: Introductionmentioning
confidence: 99%
“…Among various organic ligands, rigid dicarboxylic acids are extensively utilized to construct intriguing structures because of their strong coordination ability and diverse coordination mode . Among the different kinds of N‐containing linkers, bipyridine and their derivatives are widely employed in the construction of versatile MOFs with promising properties .…”
Section: Introductionmentioning
confidence: 99%